Validity of Hounsfield Units in Skyview Cone Beam Computed Tomography to detect bone densities at different jaw sites during implant insertion (Mustansiria Dental Journal, 2019)
The purpose of this study was to evaluate the bone densities by Hounsfield Unit at jaw sites in sky view cone beam computed tomography and to compare these values to the optimal bone densities proposed in the literature.Materials and Methods: Thirty-six patients, 15 males and 21 females were assessed; CT data for different jaw sections and regions were compared using (t-test).Results: The means of bone density in all regions are higher in male than female. The mean bone density in the anterior mandible is higher ; the mean bone densities in the four jaw regions decreased in the following order in female or male or general ( anterior mandible > anterior maxilla > posterior mandible > posterior maxilla ) .Conclusion: The bone densities assessed by HU fell into the range of optimal bone densities proposed in the literature.